192k views
2 votes
Find the average rate of change between f(-7) and f(-1) in the function f(x)=x^2+2x -8

User Adxl
by
5.3k points

1 Answer

4 votes

Answer:

- 6

Explanation:

The average rate of change of f(x) in the closed interval [ a, b ] is


(f(b)-f(a))/(b-a)

here [ a, b ] = [ - 7, - 1 ]

f(b) = f(- 1) = (- 1)² + 2(- 1) - 8 = 1 - 2 - 8 = - 9

f(a) = f(- 7) = (- 7)² + 2(- 7) - 8 = 49 - 14 - 8 = 27

Hence

average rate of change =
(-9-27)/(-1-(-7)) =
(-36)/(6) = - 6

User Manav Sharma
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.